The effect of oregano essential oil on the prevention and treatment of Salmonella pullorum and Salmonella gallinarum infections in commercial Yellow-chicken breeders - Xu, Ziheng; Wang, Can; Li, Changcheng; Wang, Min; Chen, Wenyan; Zhou, Chenyu; Wei, Ping (Frontiers in Veterinary Science, 2022)
In order to prevent pullorum disease and fowl typhoid in commercial Yellow-chicken breeders, the use of oregano essential oil (OEO) was tested for the prevention and treatment of infections of multidrug-resistant Salmonella pullorum (SP) and Salmonella gallinarum (SG). In the challenge-protection experiment, there were four groups, including group A (A1-A2, challenged, preventive dose) was supplemented with 200μL/L OEO in the drinking water during 1-35 days of age and group B (B1-B2, challenged, treatment dose) was supplemented with 400μL/L OEO during 8-12 days of age, while groups C (C1-C2, challenged) and D (unchallenged) were kept as untreated controls. And then subgroups A1, B1, and C1 were challenged with SP, while subgroups A2, B2, and C2 were challenged with SG. All birds (35 days) were weighed and necropsied, lesions were recorded and the challenging pathogens were isolated. The results showed that the positive rates of SP and SG isolation in groups A1, A2 and B1, B2 were significantly lower (P<0.05) than those of groups C1 and C2, respectively. The average body weight (BW) of groups A1 and A2 were significantly higher (P<0.05) than those of groups B1, B2 and C1, C2, respectively, but there was no significant difference (P>0.05) with that of group D. The results demonstrated that the prevention dose and the treatment dose of OEO supplemented in the drinking water could all effectively decrease infections of SP and SG and finally that the prevention could also significantly reduce the BW decline of birds challenged with SP and SG.